High power efficiency solution-processed double-layer blue phosphorescent organic light-emitting diode by controlling charge transport at the emissive layer and heterojunction - Yeoh, K.H.; Ng, C.Y.B.; Chua, C.L.; Talik, N.A.; Woon, K.L. (Wiley-VCH Verlag, 2013)
We have demonstrated an effective method of enhancing the power efficiency of double–emissive solution-processed blue phosphorescent organic light-emitting diode (PHOLED) by controlling the charge transport in the heterojunction and emissive layer. The first emissive layer consists of poly(vinylcarbazole) (PVK) and bis(4,6 difluorophenylpyridinato-N,C2)picolinatoiridium (FIrpic) mixed with 4,4′,4″-tris(N-carbazolyl)-triphenylamine (TCTA) or 1,3-bis[(4-tert- butylphenyl)-1,3,4 oxidiazolyl] phenylene (OXD-7). The second layer consists of an alcohol-soluble 2,7-bis(diphenylphosphoryl)-9,9′-spirobi[fluorene] (SPPO13) and FIrpic blend. The incorporation of OXD-7 into PVK blurs the interface between the emissive layers and widens the recombination zone while blending TCTA into PVK reduces the hole- injection barrier from PEDOT:PSS to PVK. By adding TCTA or OXD-7 into the first emissive layer, we have achieved a power efficiency of 10 lm/W and 11 lm/W, respectively, at 1000 cd/m2.